The epidemiology of love: Historical perspectives and implications for population-health research. Issue 1 (2nd January 2023) - Levin, Jeff
ABSTRACT: Since the 1990s, research studies and theoretical work have made the case for altruistic and compassionate love as a psychosocial determinant of physical and mental health and well-being. Empirical findings and the deliberations of various conferences, working groups, and think-tank initiatives have laid the groundwork for a field that has been referred to as the epidemiology of love. This article provides a narrative history of this field, beginning with early work in psychology and in sociology. These precursors include decades of psychological studies of romantic, sexual, affectional, and interpersonal bonds, preceded by the work of sociologist Pitirim Sorokin in the 1950s detailing his taxonomy of the multiple aspects and dimensions of altruism and love. More recently, research at the intersection of altruism, love, spirituality, and human flourishing has emerged, including studies of physical and mental health. Currently, funded initiatives are developing applications of this research to global population health.